PENGARUH PEMANFAATAN CAIRAN HASIL FERMENTASI SAWI PUTIH (Brassica rapa L. var Pekinensis) SEBAGAI BAHAN PENGAWET ALAMI TERHADAP KUALITAS IKAN TAMBAKAN (Helostoma temminckii C.V.) - Hendra Hendra; Soleh Hidayat (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2020)
The background of the research by situation raw materials such as fish who can very fast spoiled, so that fresh fish must to make quickly with good. Which one with use produced lactic acid bacteria from fermented white vegetable. White vegetable (Brassica rapa L. var. Pekinensis) to be contain sugar use to grown lactid acid bacteria can inhibit pathogenic bacteria at material so that potential use as material of preservative fish. The main purpose of this research were The influence white vegetable (Brassica rapa L. var. Pekinensis) as preservative material natural at quality of tambakan fish (Helostoma temminckii C.V).This research method use experimental with planning without role complete (RAL) with 6 treatments and 4 replications with test use test Duncan Double Area (WBD). The treatments consists of the P0 = control, P1 = 100 gram white vegetable/ 3% salt/ one hour soak, P2 = 200 gram white vegetable, P3 = 300 gram white vegetable, P4 = 400 gram white vegetable, P5 = 500 gram white vegetable. The result of the research: The use of natural preservatives in the form of liquid fermented white vegetable (Brassica rapa L. var. Pekinensis) very real influence the levels of water, protein, carbohydrates, color, odor, and texture tambakan fish (Helostoma temminckii C.V.). It can be seen from the results of the analysis of variance (Anava) where significant value 0,000 < α 0,05.